Keesaan Allah dalam Pemahaman Ilmu Tasawuf - Damanhuri Basyir (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
This papers describes a very general view on Tauhid in the Islamic mystical thought. The ulama from the Sufis group, like other group of ulama, intends to purify the Oneness concept of Allah. That is how such course becomes a very serious theme in their discussion. Some of the thoughts somehow contradict with their own expression and explanation, however they go to the same conclusion about Allah in relation with the unity of existence. Their discussion is around the truth of creator and the creation. This papers aims to discuss the Sufis thought in order the complexity could become clearer and the thought can be easily understood.